Malaspina expedition high-performance liquid chromatography (HPLC) phytoplankton pigment database - Mikel Latasa; Ana María Cabello; Marta Estrada; Patricija Mozetič; Pilar Rial; Francisco Rodríguez (PANGAEA, 2023)
A database of phytoplankton pigments measured by high-performance liquid chromatography (HPLC) is provided. Data belong to 139 stations of the tropical and subtropical Atlantic, Indian and Pacific oceans sampled during the seven legs of the Malaspina Expedition in 2010-2011. A vertical profile of Conductivity-Temperature-Depth (CTD) was carried out at a fixed position every day starting around 10:00 local time, down to 200 m depth. Water column samples were sampled using 12 L Niskin bottles attached to a Rosette-CTD SeaBird 9/11-plus system. Surface (3 m) waters were collected using 30 L Niskin bottles. The criteria used to select the depths of sampling in the water column along the whole expedition was based on real time profiles of fluorescence (CTD) and underwater Photosynthetically Active Radiation (PAR) recorder with a 4π Biospherical QCP2300-HP sensor installed in the Rosette (Licor co.). The six depths selected included surface (3 m), the depths receiving the 50%, 20% and 7% of PAR at the surface, the depth of the deep chlorophyll maximum (DCM), and the depth of the DCM + 20 m. For HPLC pigment quantification, 2 L or 4 L (surface samples) of seawater were filtered onto 25 mm glass fiber filters (Whatman GF/F) with low vacuum (0.03 MPa) to prevent cells from breaking. Each filter was folded, blotted dry, placed in a cryotube and frozen at -80 °C until analysis by HPLC in the lab. For pigment extraction, filters were placed in 10 mL polypropylene tubes with 2.5 mL acetone 90% and trans-ß-apo-8 extquotesingle-carotenal as internal standard and stored at -20 °C. After 24 h, the individual 10 mL tubes were placed in a beaker filled with crunched ice and sonicated. The sonicator was set at 50% power for 30 s with on: off intervals at 8:2 rate and its tip was slightly introduced into the extract. The tubes were tightly closed and stored at -20°C for 24 h. To clear the extract, a quarter of a 25 mm GFF filter, previously washed with distilled water and dried at 60 °C overnight, was introduced into a 10 μL pipette tip, which was tightly inserted into a 5 mL tip inserted, in turn, into a 10 mL polypropylene centrifuge tube. The extract with the pigment filter were transferred into this cleaning column. The system was closed and, after centrifugation at 3000 rpm for 3 min, 1 mL of clean extract from the bottom of the centrifuge tube was transferred to an autosampler vial. A large volume injection procedure was performed to improve the detection and quantification of pigments (Latasa, 2014). The Agilent (Waldbronn, Germany) series 1200 chromatographic system used consisted of a G1311A quaternary pump, a G1367C autosampler with a 100 μL capillary loop, a G1316B column thermostat, and a G1315C diode array detector. An additional 2 mL loop with 0.5 mm internal diameter was placed in the autosampler between the needle seat and the Rheodyne changing valve. The system was governed by Agilent Chemstation v. B.04.03 software. A 150 exttimes 4.6 mm, 3.5 μm particle, Symmetry C8 (Waters) column was used for analysis. The reagents used were acetonitrile, methanol, and acetone (HPLC grade, Carlo-Erba), pyridine (analysis grade, Carlo-Erba) and 0.2 μm filtered Milli-Q water (Millipore). The first injection of the day was made with acetone and always discarded. Acetone with internal standard was injected at the beginning and end of each daily batch of samples. HPLC analysis was based on the method of Zapata et al. (2000) with slight modifications. Chlorophylls a and b families and derivatives were quantified at 664 nm to avoid the potential interference of contaminant carotenoids. Carotenoids and the chlorophyll c - family were quantified at 474 nm. Since divinyl and monovinyl chlorophyll b co-eluted in a single chromatographic peak, the 454 nm and 484 nm signals were used to quantify the contribution of the two pigments applying the procedures of Latasa et al. (1996). During the analysis of the Malaspina samples, the eluent system was modified to improve separation of alloxanthin, which co-eluted with a compound optically derivative of 19 extquotesinglehexanoyloxyfucoxanthin in the analyses of legs 1 and 2, and is, therefore, not reported for those legs.